2017
DOI: 10.1002/jcla.22120
|View full text |Cite
|
Sign up to set email alerts
|

Serum galectin‐3 level as a marker of thrombogenicity in atrial fibrillation

Abstract: In conclusion, in the setting of persistent AF, serum galectin-3 levels are associated with presence of SEC and LAAFV on TEE. Our findings suggest that serum galectin-3 level may have a place in thromboembolism risk stratification in persistent AF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…This association was further confirmed in another study using delayed enhancement magnetic resonance imaging, which demonstrated an atrial electromechanical delay in PAF patients [35]. Moreover, recent studies showed that increased Gal-3 levels correlated with increased thrombogenicity in persistent AF patients as reflected by reduced LA appendage flow velocity, appendage remodeling, and thrombus formation in transesophageal echocardiography [36, 37]. These findings suggested that baseline Gal-3 levels reflect the risk of stroke in AF patients.…”
Section: Discussionmentioning
confidence: 67%
“…This association was further confirmed in another study using delayed enhancement magnetic resonance imaging, which demonstrated an atrial electromechanical delay in PAF patients [35]. Moreover, recent studies showed that increased Gal-3 levels correlated with increased thrombogenicity in persistent AF patients as reflected by reduced LA appendage flow velocity, appendage remodeling, and thrombus formation in transesophageal echocardiography [36, 37]. These findings suggested that baseline Gal-3 levels reflect the risk of stroke in AF patients.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, in patients with AF, high Galectin‐3 levels were closely related to LAA thrombi. Kocyigit et al 21 found that high serum levels of Galectin‐3 predicted the presence of spontaneous atrial echo‐contrast or LAA thrombi. In a subanalysis of the ARISTOTLE study with 1996 AF patients, there was a significant association between Galectin‐3 and mortality 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in patients with AF, high Galectin-3 levels were closely related to LAA thrombi. Kocyigit et al 21 found that high serum levels of Galectin-3…”
Section: Gdf-15 and Galectin-3mentioning
confidence: 99%
“…Gal-3 value was higher in patients with AF than those with sinus rhythm [40]. Gal-3 was also correlated with AF duration and left atrial diameter [41], and significantly higher in the presence of spontaneous echo contrast (SEC) and left atrial thrombus [42].…”
Section: Gal-3 In Atrial Fibrillation (Af)mentioning
confidence: 91%